Multiple regression analysis for evaluation of the effect of insect populations on upland rice yield - Ferreira, Evane; Martins, José Francisco da Silva; Neto, Sinval Silveira; Carvalho, José Ruy Porto de (Pesquisa Agropecuaria Brasileira, 2014)
The influence of insects on rice yield was studied using multiple regression step wise procedure. The equations with maximum values of coefficient of determinations (R2) were selected. The regression equations established for 1977/78. 1978/79, 1979/80 indicated that the insect populations were responsible for 23.6, 28.4 and 34.6% grain yield loss, respectively. The results further indicated that the presence of some other insects showed positive effect on yield.
Keywords: economic entomology; losses and benefits estimations